Analisis Implementasi Kebijakan ASI Eksklusif Dalam Pencapaian Target ASI Eksklusif di Kota Padang - Annisa Wahyuni; Ressa Oashttamadea (Iris Journal of Health Information Management, 2022)
The government's efforts in achieving the target of exclusive breastfeeding have been stated in Government Regulation no. 33 of 2012. In Padang city, Perwako Regulation Number 7 of 2015 on Provision of Space for Breastfeeding and or Expressing Breastmilk has been issued. This is a form of efforts to accelerate the achievement of the target coverage of exclusive breastfeeding. This study aims to analyze the implementation of the exclusive breastfeeding policy in achieving the target in the city of Padang. In this study, an analytical study will be carried out on the achievement of exclusive breastfeeding coverage and the implementation of PP No. 33/2012 and Perwako in Padang City. Achievements from the exclusive breastfeeding program coverage in the city of Padang, obtained an average of 79.40%. However, this figure cannot be generalized because there is still an equity gap that occurs in several working areas of Puskesmas in Padang City. In the last three years (2017- 2019) the achievements in several health centers have experienced significant fluctuations and decreases, including at Ulak Karang Puskesmas where in 2019 it was 54.5%. The same thing happened at Puskesmas Alai, and Puskesmas Lubuk Buaya experienced a sharp decline from 2017 to 2019 from 77.22% to 52%. Policy implementation has not been carried out properly. So it is necessary to carry out evaluation and follow-up related to the achievements over the last few years (2017-2019), increase cooperation and coordination between the government, health agencies, health workers, and community leaders, and affirmation in determining administrative and written sanctions to support efforts to accelerate the achievement of breastfeeding targets.